PELANGGARAN HAK MORAL ATAS KARYA CIPTA DALAM PENERBITAN ELEKTRONIK - IMAS ROSIDAWATI WIRADIRJA (Fakultas Hukum Universitas Pasundan, 2013)
Moral Rights protection is getting ignored in the era of global economy, specially since the beginning the emergence of the Information Technology revolution is marked by the use of the Internet as a means of communication. In the era when copyrights exploitation is becoming more intensive, complex, and multifacet, the appreciation of moral rights is being ignored. Society can access easily in the form of information products and other digital products which can be directly received. However, copyright infringement for e-books are often overlooked, because it's so easy to copy and modify digital product. Issues related to moral rights are the work of the e-book is translated without permission, and then up loaded in the Internet. This is an issue that occurs in cyberspace. Copyright is the legal protection extended to the owner of the rights in an original work that he has created on e-book. Nowadays, people can easily access and obtain digital information such as e-book which is published and reproduced without respecting the copyrights of it. The issue related to the moral rights is that the e-book is translated without getting legal permission from the author, and publish it on the internet. This is a law issue in the realm of internet. Copyrights privides legal protection to the original owner of the e-book. That is why; the objective of this study is to find and analyze copyrights breaching happens in cyberspace and what efforts needed to examine prevention of moral rights infringement under Indonesia regulations.Keywords: Moral Rights; Copyright; Electronic Publishing; E-Book TranslationABSTRAKPerlindungan Hak Moral semakin terabaikan dalam era ekonomi global, terutama sejak munculnya revolusi Teknologi Informasi (TI) yang ditandai dengan maraknya penggunaan Internet sebagai sarana komunikasi. Dalam era digital eksploitasi karya cipta semakin intensif, kompleks, dan multifacet, sehingga cenderung mengabaikan penghormatan terhadap hak moral pencipta. Dewasa ini, masyarakat dapat dengan mudah mengakses dan mendapatkan informasi dalam bentuk produk informasi digital termasuk buku elektronik (e-book). Akan tetapi, hal ini menyebabkan terjadinya pelanggaran terhadap Hak Cipta buku elektronik (e-book) yang sering kali diabaikan, hal ini terjadi karena begitu mudahnya orang untuk menyalin dan memodifikasi produk digital tersebut. Isu yang terkait dengan hak moral adalah karya e-book tersebut diterjemahkan tanpa izin pengarangnya, dan kemudian dimuat di Internet. Ini adalah permasalahan hukum yang terjadi di dunia maya. Hak Cipta memberikan perlindungan hukum kepada pemilik hak dalam karya asli seperti pada e-book tersebut. Oleh karena itu, tujuan dari penelitian ini adalah untuk menemukan dan menganalisis pelanggaran Hak Cipta di dunia maya dan meneliti upaya pencegahan terhadap pelanggaran hak moral tersebut melalui peraturan hukum di Indonesia.Kata Kunci : Hak Moral; Hak Cipta; Penerbitan Elektronik; Terjemahan E-Book